HUBUNGAN TUJUAN MATA PELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) DAN MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMPN 3 TALIWANG KABUPATEN SUMBAWA BARAT - Yuliana, Fitria (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study aims to analyze the relationship between the objectives of social science subjects (IPS) and Civic Education subjects (PKN) at SMPN 3 Taliwang. This research is a Qualitative Field Study Research. Data collection uses interview, observation, and documentation techniques. The data that has been obtained is analyzed qualitatively by data reduction, data presentation, and drawing conclusions/verification. The results of the study include 1) there is a relationship between the Social Sciences (IPS) and Civic Education (PKN) subjects that the two subjects have similarities, namely the Social Sciences Education (IPS) and Civic Education (PKN) both study about the social life of the community. 2) Social Sciences (IPS) and Civic Education (PKN) subjects have the same goal, namely character building. Specifically, in the Civic Education Subject (PKN), it is more about shaping the character of students who are ethical, polite, and become obedient citizens in state life. Meanwhile, in the Social Science Curriculum (IPS), students are formed so that they are ready to face social problems, face problems in social life, such as juvenile delinquency, drug problems, and so on.